Pengaruh Influencer, Citra Merek, Harga, dan Kualitas Produk Terhadap Keputusan Pembelian Produk Skincare Somethinc (Studi Kasus Mahasiswa Kecamatan Lowokwaru, Kota Malang) - Pandora, Calista Mina; Arifin, Rois; Rachmadi, Kartika Rose (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of influencers, brand image, price, and product quality on the purchase decision of Somethinc skincare products. The research was conducted on university students residing in the Lowokwaru District of Malang City. This study employed a quantitative approach with data collected through an online questionnaire from 100 respondents. The analysis method used was multiple linear regression. The results show that simultaneously, all independent variables significantly affect the purchase decision. Partially, influencer, brand image, and product quality had a significant effect, while price did not. These findings provide strategic implications for local skincare companies to enhance digital marketing and maintain product quality Keywords: Influencer, Brand Image, Price, Product Quality, Purchase Decision